2017
DOI: 10.4174/astr.2017.92.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of sustained perivascular delivery of paclitaxel on neointimal hyperplasia in the jugular vein after open cutdown central venous catheter placement in rats

Abstract: PurposeInhibitory effect of paclitaxel on neointimal hyperplasia after open cutdown has not been elucidated.MethodsFor the control group (n = 16), silicone 2.7-Fr catheters were placed via the right external jugular vein with the cutdown method. For the treatment group (n = 16), a mixture of 0.65 mg of paclitaxel and 1 mL of fibrin glue was infiltrated around the exposed vein after cutdown. After scheduled intervals (1, 2, 4, and 8 weeks), the vein segment was harvested and morphometric analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…33 Last but not least, in the event of repeated insertions, venous cutdown is inevitably associated with a progressive depletion of the vascular patrimony due to venous thrombosis and/or stenosis. [34][35][36][37] Venous cutdown is currently replaced by ultrasound-guided techniques, which are safer, more effective and more cost-effective. [38][39][40] Today, the gold-standard in terms of technique of CVAD insertion is represented by the ultrasound-guided percutaneous technique, 3,[41][42][43] which is based on ultrasound (US) use to locate the vein, study its characteristics (course, caliber, presence of valves / endoluminal formations), measure the distance of the same from the skin surface, direct the path of the needle and also control the introduction of the guide wire in real time.…”
Section: Indications For Insertion and Selection Of The Cvadmentioning
confidence: 99%
“…33 Last but not least, in the event of repeated insertions, venous cutdown is inevitably associated with a progressive depletion of the vascular patrimony due to venous thrombosis and/or stenosis. [34][35][36][37] Venous cutdown is currently replaced by ultrasound-guided techniques, which are safer, more effective and more cost-effective. [38][39][40] Today, the gold-standard in terms of technique of CVAD insertion is represented by the ultrasound-guided percutaneous technique, 3,[41][42][43] which is based on ultrasound (US) use to locate the vein, study its characteristics (course, caliber, presence of valves / endoluminal formations), measure the distance of the same from the skin surface, direct the path of the needle and also control the introduction of the guide wire in real time.…”
Section: Indications For Insertion and Selection Of The Cvadmentioning
confidence: 99%
“…To prevent smooth muscle hyperplasia-related restenosis of vessels after mechanical balloon dilatation, drug-coated balloons with paclitaxel are widely applied clinically, 55 and paclitaxel treatment of the jugular vein in one rat model significantly reduced pericatheter fibrin sheath formation and kept venous luminal patency. 56 However, the toxicity and side effects on long-term patient mortality are a concern and need further investigation. 57 The present study showed that treatment with a combination of DNase I and the antibiotic oxacillin can significantly reduce bacterial colonization and fibrin sheath formation, possibly representing a new strategy by which to treat catheter-related thrombosis clinically.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat cranial model, scaffolds comprising FG loaded with 5 µg of embryonically derived heparin sulfate were applied for the enhancement of bone repair [ 20 ]. Kim et al [ 21 ] revealed that sustained perivascular delivery of paclitaxel with FG effectively inhibited neointimal hyperplasia in rat jugular vein after open cutdown. This study provides sustained release methods for autologous bone graft and growth factor-based therapies.…”
Section: Discussionmentioning
confidence: 99%